2018
DOI: 10.1111/1756-185x.13251
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐ and long‐chain acylcarnitines are associated with osteoarthritis severity and arterial stiffness in end‐stage osteoarthritis patients: a case‐control study

Abstract: We found decreased levels of acylcarnitines in OA patients. Furthermore, medium-and long-chain acylcarnitines associated independently with arterial stiffness and were related to radiographic severity of OA. Thus, acylcarnities might play an important role in the association between OA and CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…C2, the acetylated form of carnitine, plays an integral role in the transport of fatty acids to the mitochondria, where they are oxidized to generate acetyl coenzyme A (CoA) for energy production . Recently, Tootsi et al studied 70 end‐stage OA patients prior to joint replacement and 82 age‐matched controls and found that levels of medium‐ and long‐chain acylcarnitines were significantly decreased in OA patients and were associated with OA radiographic severity. We previously studied the metabolic profiles of synovial fluid samples of 80 end‐stage OA patients who underwent TJR and found that there were two distinct groups, with one group having significantly lower concentrations of all the acylcarnitines measured in the study, as well as a high prevalence of metabolic‐related and cardiovascular diseases .…”
Section: Discussionmentioning
confidence: 99%
“…C2, the acetylated form of carnitine, plays an integral role in the transport of fatty acids to the mitochondria, where they are oxidized to generate acetyl coenzyme A (CoA) for energy production . Recently, Tootsi et al studied 70 end‐stage OA patients prior to joint replacement and 82 age‐matched controls and found that levels of medium‐ and long‐chain acylcarnitines were significantly decreased in OA patients and were associated with OA radiographic severity. We previously studied the metabolic profiles of synovial fluid samples of 80 end‐stage OA patients who underwent TJR and found that there were two distinct groups, with one group having significantly lower concentrations of all the acylcarnitines measured in the study, as well as a high prevalence of metabolic‐related and cardiovascular diseases .…”
Section: Discussionmentioning
confidence: 99%
“…It is regulated by controlling mitochondrial uptake of fatty acids by the carnitine shuttle. Tootsi et al [34] studied 70 end-stage OA patients before joint replacement and 82 age-matched controls and found that serum levels of medium- and long-chain acylcarnitines were significantly decreased in OA patients and were associated with OA radiographic severity. Further, this study showed that the acylcarnitines were associated arterial stiffness, suggesting acylcarnitines might play an important role in the link between OA and cardiovascular diseases.…”
Section: Energy Metabolic Pathwaysmentioning
confidence: 99%
“…The most common reported changes is an increase in blood concentration of LC acylcarnitines in individuals with age-related diseases [ 11 – 14 ]. Dysregulation of acylcarnitine homeostasis has been tied to a variety of age-related diseases, including cardiovascular disease [ 11 , 12 , 15 ], type II diabetes mellitus [ 13 , 16 , 17 ], osteoarthritis [ 18 ], chronic obstructive pulmonary disease [ 19 ], macular degeneration [ 14 ], glaucoma [ 20 ] and Alzheimer’s disease [ 21 – 23 ]. In addition to the association with age-related diseases, abnormal acylcarnitine levels are associated with activation of inflammation [ 24 ] and mitochondrial dysfunction [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%